Analysis Of People's Business Credit (KUR) In Effectiveness Of Increasing Kur Distribution (Case Study Of The State Savings Bank (BTN) Kc Sukabumi) - Zakiah Nur Latifah zakiahnurlatifahsmi@gmail.com; Venita Sofiani (LPPM Universitas Buddhi Dharma, 2024)
People's Business Credit (KUR) is a government program to help MSMEs access financing. However, the State Savings Bank (BTN) Sukabumi Branch Office faces challenges in achieving its distribution target, with significant fluctuations and decreases in the realization of KUR. This study aims to analyze the effectiveness of KUR distribution, identify the factors that cause the non-achievement of the target, and formulate a strategy to increase the realization of KUR in BTN KC Sukabumi. The scope of the research includes KUR's business processes and distribution performance for the period January to May 2024. The research method used is qualitative descriptive, with data collection through observation, interviews, and documentation analysis. The results of the study show that the KUR distribution process has a structured procedure with credit analysis using the 5C and 7P methods. However, the realization of KUR distribution has decreased drastically, from 146% in January to only 0.6% in April. The main factors causing this are the tightening of distribution criteria and the limitations of service areas. To overcome these challenges, a comprehensive strategy is needed including intensification of local marketing, optimization of distribution networks, product innovation, strengthening partnerships, and utilization of technology. The implementation of this recommendation is expected to increase the effectiveness of KUR distribution and support the development of MSMEs in the Sukabumi area.